Steel plate for automobile chassis part and preparation process of steel plate
By optimizing the material composition and heat treatment process of steel plates for automotive chassis parts, combined with the preparation of ceramic coatings, the problems of insufficient toughness and uneven heat treatment of existing steels have been solved, and high strength, fatigue resistance and heat corrosion resistance have been improved.
Patent Information
- Application Number
- CN202510123245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the pursuit of ultra-high strength and porosity, existing steel for automotive chassis parts lacks toughness and is difficult to treat thicker steel plates evenly with a single heat treatment, resulting in uneven internal stress of the material and affecting service life.
By optimizing the composition of the steel plate material, adding microalloy elements vanadium and niobium, refining the grains and strengthening the precipitation, and using multi-stage heat treatment with austenitization, martensite formation, and stable partitioning. Meanwhile, tetraisopropyl titanate and ethyl silicate were used as precursors, ZrO2 and Al2O3 nanoparticles were added, and the ceramic coating was prepared by a sol-gel process.
It significantly improves the strength and fatigue resistance of the steel plate, improves the comprehensive performance and heat and corrosion resistance of the material, and extends the service life.
Smart Images

Figure BDA0005259361310000101 
Figure BDA0005259361310000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultra-high-strength steel materials and relates to a steel plate for automobile chassis parts and a preparation process thereof. Background Art
[0002] Steel for automobile chassis parts plays a key role in modern automobile manufacturing. It not only needs to withstand complex mechanical stresses and harsh environmental conditions to ensure that it can effectively transmit and buffer vibrations when the vehicle is driving at high speed or on bumpy roads, but also ensure the reliability and safety of the chassis structure. In addition, the ultra-high hole expansion rate of steel is particularly important in the stamping process, which enables the material to have excellent forming capabilities while maintaining strength, thereby meeting the needs of modern automobile lightweighting and structural optimization. Steel with a high hole expansion rate is particularly critical for manufacturing parts with complex shapes.
[0003] At present, the technology for preparing steel for automobile chassis covers multiple processing steps from smelting to finished steel plates. In the smelting stage, the ratio of the alloying elements is precisely adjusted to improve the strength and toughness of the steel, while enhancing its hole expansion performance. The surface oxide scale is removed through smelting, casting, pickling and other processes to improve its plasticity, surface quality and process performance. The optimization of these steps ensures the excellent performance of the steel in subsequent processing and use. In addition, the precisely controlled process parameters help to achieve the uniformity and stability of the steel, enabling it to maintain a high level of performance in various complex processing environments.
[0004] Although the existing steel plate preparation process is capable of producing high-strength steel, there are still some shortcomings. First, the addition and control of alloying elements are demanding, especially in the pursuit of ultra-high strength and hole expansion rate, which may lead to insufficient toughness of the steel plate. In addition, a single heat treatment process is sometimes difficult to completely and evenly treat thicker steel plates, resulting in uneven internal stress of the material, affecting the service life. In order to solve these problems, continuous innovation and improvement in composition improvement and process research and development are needed to further improve the overall performance and service life of steel. Summary of the invention
[0005] The present invention relates to a steel plate for automobile chassis parts and a preparation process thereof, and belongs to the technical field of ultra-high strength steel materials. The present invention optimizes the steel plate material, adds microalloy elements vanadium and niobium, refines the grains and strengthens the precipitation, thereby improving the strength and fatigue resistance of the steel plate. Through austenitization, martensite formation, and multi-stage heat treatment with stable partitioning, the structure of the steel plate is optimized, forming a microstructure combining high-strength tempered martensite and stable residual austenite, thereby improving the comprehensive performance of the material. Using tetraisopropyl titanate and ethyl silicate as precursors, adding ZrO2 and Al2O3 nanoparticles, and preparing a ceramic coating through a sol-gel process, the mechanical properties and heat resistance and corrosion resistance of the material are further enhanced.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A steel plate for automobile chassis parts, the steel plate composition comprises: 0.03-0.05wt% C, 0.01-0.025wt% Si, 0.2-0.45wt% Mn, 0.02-0.1wt% V, 0.01-0.05wt% Nb, 0.01-0.025wt% P, 0.005-0.015wt% S, the balance is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite formation, partition stabilization multi-stage heat treatment and sol-gel process.
[0008] Furthermore, the preparation process of the steel plate for automobile chassis parts comprises the following steps:
[0009] Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
[0010] As a preferred technical solution of the present invention, the hot rolling is to heat the ingot to 1100-1300°C and maintain it for 40-60 minutes; the pickling cold rolling is to pass the hot rolled steel plate through a pickling line, pickle it with a 1-5wt% hydrochloric acid solution for 1-5 minutes to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 600-700°C.
[0011] As a preferred technical solution of the present invention, the heat treatment is: heating the steel plate at 850-950°C to transform the structure of the steel into austenite; rapidly cooling to 200-250°C slightly lower than the martensite starting temperature, maintaining for 30-60 minutes, generating part of the martensite, and retaining a certain amount of untransformed austenite; then heating to a moderate partitioning temperature of 250-450°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling to room temperature to form high-strength tempered martensite and stable residual austenite.
[0012] As a preferred technical solution of the present invention, the coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are:
[0013] (1) Dissolve the precursor material in anhydrous ethanol, mix well, stir at 20-40° C., adjust the pH to 2-4 with 1 M dilute hydrochloric acid, and let stand for 20-60 hours to obtain a sol;
[0014] (2) adding nanoparticles and a dispersant to the sol, stirring and ultrasonicating for 30-60 minutes to prepare a nanosol;
[0015] (3) using dip coating, spray coating or spin coating to evenly cover the surface of the steel plate with the nanosol, and drying it at 20-80° C. to convert the nanosol into a gel to initially form a coating;
[0016] (4) The coated steel plate is heated and sintered to convert the gel into a dense ceramic coating.
[0017] As a preferred technical solution of the present invention, the precursor material in step (1) is tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:5-10.
[0018] As a preferred technical solution of the present invention, the dispersant in step (2) is at least one of polyvinyl alcohol, polyacrylic acid, and polyethylene glycol; the nanoparticles are ZrO2 and Al2O3; and the mass ratio of the nanoparticles, the dispersant, and the sol is 5-20:1-10:70-94.
[0019] As a preferred technical solution of the present invention, the temperature of the heating and sintering in step (4) is 200-500°C.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention optimizes the steel plate material to obtain high strength and high toughness. First, the low carbon content helps to improve the toughness of the steel and provides a good foundation for the welding performance of the steel. The addition of silicon and manganese improves the strength of the steel while maintaining a certain ductility and processing performance, making it less likely for the steel plate to have cracks or other processing defects during cold rolling and forming. Secondly, the addition of trace amounts of vanadium (V) and niobium (Nb) can significantly improve the strength and fatigue resistance of the steel through grain refinement and precipitation strengthening mechanisms, making it more suitable for the preparation of automobile chassis with high hole expansion rates.
[0022] (2) The present invention uses a multi-stage heat treatment with precise control to regulate the temperature and time of each stage, so that the steel plate is heated evenly, and the residual stress of the steel plate is effectively reduced by multiple heating and cooling, thereby improving the strength and toughness of the steel plate. The steel is first heated to the austenitizing temperature, so that the structure of the steel is completely transformed into austenite, and then quickly cooled to a temperature slightly lower than the martensite starting temperature, so that part of the austenite is transformed into martensite to form a high-strength martensite phase. By controlling the cooling rate and the holding time, part of the martensite is generated and a certain amount of untransformed austenite is retained, which helps to improve the toughness of the material, because the untransformed austenite can be further transformed into martensite through strain-induced phase transformation (TRIP effect) during the deformation process, absorbing energy, thereby improving the impact toughness. Heating at a moderate temperature allows the carbon in the martensite to diffuse into the untransformed austenite, thereby stabilizing the austenite, effectively improving the stability of the residual austenite, allowing it to exist at room temperature, and providing good toughness and ductility during subsequent use.
[0023] (3) Using tetraisopropyl titanate and ethyl silicate as precursors, adding ZrO2 and Al2O3 nanoparticles, and preparing ceramic coatings through sol-gel process, the mechanical properties and heat resistance and corrosion resistance of the material are further enhanced. The sol-gel process helps to form a uniform and dense coating. This dense structure can effectively resist external mechanical damage and improve the durability of the material. ZrO2 and Al2O3 nanoparticles have extremely high hardness and strength. When dispersed in the coating, they can significantly improve the hardness and wear resistance of the coating; not only does it improve the high temperature resistance of the material, zirconium oxide and aluminum oxide show excellent corrosion resistance in many corrosive environments, and the dense coating can act as a physical barrier to prevent the corrosive medium from penetrating into the base material, thereby extending the service life of the material. DETAILED DESCRIPTION
[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0025] In the following examples and comparative examples, the polyvinyl alcohol was purchased from Shanxi Sanwei Shengtai New Material Technology Co., Ltd.; polyacrylic acid was purchased from Shandong Kasong New Material Co., Ltd. with the item number PAA; polyethylene glycol was purchased from Zhongrun (Shandong) New Material Co., Ltd. with the item number 97-97-1.
[0026] Example 1
[0027] A steel plate for automobile chassis parts, the steel plate composition includes: 0.04wt% C, 0.015wt% Si, 0.3wt% Mn, 0.05wt% V, 0.02wt% Nb, 0.02wt% P, 0.01wt% S, and the balance is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite formation, partition stabilization multi-stage heat treatment and sol-gel process.
[0028] The preparation process of the steel plate for automobile chassis parts comprises the following steps:
[0029] Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
[0030] The hot rolling is to heat the ingot to 1200°C and maintain it for 50 minutes; the pickling cold rolling is to pass the hot rolled steel plate through a pickling line, pickle it with a 2wt% hydrochloric acid solution for 3 minutes to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 650°C.
[0031] The heat treatment is as follows: heating the steel plate at 900°C to transform the structure of the steel into austenite; rapidly cooling to 220°C, slightly lower than the martensite starting temperature, and maintaining for 40 minutes to generate part of the martensite and retain a certain amount of untransformed austenite; then heating to a moderate partitioning temperature of 350°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling to room temperature to form high-strength tempered martensite and stable residual austenite.
[0032] The coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are:
[0033] (1) The precursor material was dissolved in anhydrous ethanol, mixed evenly, stirred at 30° C., the pH was adjusted to 3 with 1 M dilute hydrochloric acid, and allowed to stand for 40 h to obtain a sol;
[0034] (2) adding nanoparticles and a dispersant into the sol, stirring and ultrasonicating for 50 minutes to prepare a nanosol;
[0035] (3) using dip coating to evenly cover the surface of the steel plate with the nanosol, drying it at 20-80° C. to convert the nanosol into a gel, and initially forming a coating with a thickness of 300 nm;
[0036] (4) The coated steel plate is heated and sintered at 350°C to convert the gel into a dense ceramic coating.
[0037] The precursor materials in step (1) are tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:8.
[0038] The dispersant in step (2) is polyvinyl alcohol; the nanoparticles are ZrO2 and Al2O3 in a mass ratio of 1:1; the mass ratio of the nanoparticles, the dispersant and the sol is 12:5:83.
[0039] Example 2
[0040] A steel plate for automobile chassis parts, the steel plate composition comprises: 0.03wt% C, 0.01wt% Si, 0.2-0.45wt% Mn, 0.02wt% V, 0.01wt% Nb, 0.01wt% P, 0.005wt% S, the balance is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite formation, partition stabilization multi-stage heat treatment and sol-gel process.
[0041] The preparation process of the steel plate for automobile chassis parts comprises the following steps:
[0042] Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
[0043] The hot rolling is to heat the ingot to 1100°C and maintain it for 40 minutes; the pickling cold rolling is to pass the hot rolled steel plate through a pickling line, pickle it with a 1wt% hydrochloric acid solution for 5 minutes to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 600°C.
[0044] The heat treatment is as follows: heating the steel plate at 850°C to transform the structure of the steel into austenite; rapidly cooling to 200°C, slightly lower than the martensite starting temperature, and maintaining for 30 minutes to generate part of the martensite and retain a certain amount of untransformed austenite; then heating to a moderate partitioning temperature of 250°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling to room temperature to form high-strength tempered martensite and stable residual austenite.
[0045] The coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are:
[0046] (1) The precursor material was dissolved in anhydrous ethanol, mixed evenly, stirred at 20° C., the pH was adjusted to 2 with 1 M dilute hydrochloric acid, and allowed to stand for 20 h to obtain a sol;
[0047] (2) adding nanoparticles and a dispersant into the sol, stirring and ultrasonicating for 30 minutes to prepare a nanosol;
[0048] (3) The nanosol was evenly coated on the surface of the steel plate by dip coating and dried at 20°C to convert the nanosol into gel, thereby initially forming a coating with a thickness of 300 nm;
[0049] (4) The coated steel plate is heated and sintered at 200°C to convert the gel into a dense ceramic coating.
[0050] The precursor materials in step (1) are tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:5.
[0051] The dispersant in step (2) is polyacrylic acid; the nanoparticles are ZrO2 and Al2O3 in a mass ratio of 3:7; the mass ratio of the nanoparticles, the dispersant and the sol is 5:1:94.
[0052] Example 3
[0053] A steel plate for automobile chassis parts, the steel plate composition includes: 0.05wt% C, 0.025wt% Si, 0.45wt% Mn, 0.1wt% V, 0.05wt% Nb, 0.025wt% P, 0.015wt% S, the balance is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite formation, partition stabilization multi-stage heat treatment and sol-gel process.
[0054] The preparation process of the steel plate for automobile chassis parts comprises the following steps:
[0055] Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
[0056] The hot rolling is to heat the ingot to 1300°C and maintain it for 60 minutes; the pickling cold rolling is to pass the hot-rolled steel plate through a pickling line, pickle it with a 5wt% hydrochloric acid solution for 1 minute to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 700°C.
[0057] The heat treatment is as follows: heating the steel plate at 950°C to transform the structure of the steel into austenite; rapidly cooling to 250°C, slightly lower than the martensite starting temperature, and maintaining for 60 minutes to generate part of the martensite and retain a certain amount of untransformed austenite; then heating to a moderate partitioning temperature of 450°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling to room temperature to form high-strength tempered martensite and stable residual austenite.
[0058] The coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are:
[0059] (1) The precursor material was dissolved in anhydrous ethanol, mixed evenly, stirred at 40° C., the pH was adjusted to 4 with 1 M dilute hydrochloric acid, and allowed to stand for 60 h to obtain a sol;
[0060] (2) adding nanoparticles and a dispersant into the sol, stirring and ultrasonicating for 60 minutes to prepare a nanosol;
[0061] (3) The nanosol was evenly coated on the surface of the steel plate by spraying, and dried at 80° C. to convert the nanosol into gel, thereby initially forming a coating with a thickness of 300 nm;
[0062] (4) The coated steel plate is heated and sintered at 500°C to convert the gel into a dense ceramic coating.
[0063] As a preferred technical solution of the present invention, the precursor materials in step (1) are tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:10.
[0064] The dispersant in step (2) is polyethylene glycol; the nanoparticles are ZrO2 and Al2O3 in a mass ratio of 1:4; the mass ratio of the nanoparticles, the dispersant and the sol is 20:10:70.
[0065] Example 4
[0066] A steel plate for automobile chassis parts, the steel plate composition includes: 0.03wt% C, 0.01wt% Si, 0.45wt% Mn, 0.1wt% V, 0.01wt% Nb, 0.01wt% P, 0.015wt% S, the balance is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite formation, partition stabilization multi-stage heat treatment and sol-gel process.
[0067] The preparation process of the steel plate for automobile chassis parts comprises the following steps:
[0068] Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
[0069] The hot rolling is to heat the ingot to 1300°C and maintain it for 40 minutes; the pickling cold rolling is to pass the hot rolled steel plate through a pickling line, pickle it with a 2wt% hydrochloric acid solution for 2 minutes to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 700°C.
[0070] The heat treatment is as follows: heating the steel plate at 950°C to transform the structure of the steel into austenite; rapidly cooling to 200°C, slightly lower than the martensite starting temperature, and maintaining for 30 minutes to generate part of the martensite and retain a certain amount of untransformed austenite; then heating to a moderate partitioning temperature of 450°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling to room temperature to form high-strength tempered martensite and stable residual austenite.
[0071] The coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are:
[0072] (1) The precursor material was dissolved in anhydrous ethanol, mixed evenly, stirred at 40° C., the pH was adjusted to 2 with 1 M dilute hydrochloric acid, and allowed to stand for 20 h to obtain a sol;
[0073] (2) adding nanoparticles and a dispersant into the sol, stirring and ultrasonicating for 60 minutes to prepare a nanosol;
[0074] (3) using spin coating to evenly cover the surface of the steel plate with the nanosol, and drying it at 80°C to convert the nanosol into a gel, thereby initially forming a coating with a thickness of 300 nm;
[0075] (4) The coated steel plate is heated and sintered at 300°C to convert the gel into a dense ceramic coating.
[0076] The precursor materials in step (1) are tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:7.
[0077] In step (2), the dispersant is polyvinyl alcohol and polyacrylic acid in a mass ratio of 1:1; the nanoparticles are ZrO2 and Al2O3 in a mass ratio of 7:3; and the mass ratio of the nanoparticles, the dispersant and the sol is 16:2:82.
[0078] Comparative Example 1
[0079] On the basis of Example 1, the composition of the steel plate is changed to: 0.04wt% C, 0.015wt% Si, 0.3wt% Mn, 0.07wt% Nb, 0.02wt% P, 0.01wt% S, and the remainder is Fe and unavoidable impurity elements, and the rest is consistent with Example 1.
[0080] Comparative Example 2
[0081] On the basis of Example 1, the composition of the steel plate is changed to: 0.04wt% C, 0.015wt% Si, 0.3wt% Mn, 0.07wt% V, 0.02wt% P, 0.01wt% S, and the remainder is Fe and unavoidable impurity elements, and the rest is consistent with Example 1.
[0082] Comparative Example 3
[0083] On the basis of Example 1, the steel is not subjected to heat treatment, and the rest is consistent with Example 1.
[0084] Comparative Example 4
[0085] On the basis of Example 1, only tetraisopropyl titanate was added as the precursor material, and the mass ratio of tetraisopropyl titanate to anhydrous ethanol was 1:4. The rest was consistent with Example 1.
[0086] Comparative Example 5
[0087] On the basis of Example 1, only ethyl silicate was added to the precursor material, and the mass ratio of ethyl silicate to anhydrous ethanol was 1:4. The rest was consistent with Example 1.
[0088] Comparative Example 6
[0089] On the basis of Example 1, only ZrO2 is added as nanoparticles, and the rest is consistent with Example 1.
[0090] Comparative Example 7
[0091] On the basis of Example 1, only Al2O3 is added as nanoparticles, and the rest is consistent with Example 1.
[0092] Performance Test:
[0093] The surface hardness is tested according to GB / T 7997-2014 "Test method for Vickers hardness of cemented carbide".
[0094] The "Tensile test of metal materials" in standard GB / T 228.1 tests the tensile strength and elongation at break at room temperature.
[0095]
[0096]
[0097] By comparing the test results of Examples 1-4 and Comparative Examples 1-2, it can be seen that the present invention adds microalloying elements vanadium and niobium to improve the hardness and tensile strength of the steel plate; from the test results of Examples 1-4 and Comparative Example 3, it can be seen that through multi-stage heat treatment, the hardness and toughness of the steel are significantly improved; from the test results of Examples 1-4 and Comparative Examples 4-7, it can be seen that using tetraisopropyl titanate and ethyl silicate as precursors, adding ZrO2 and Al2O3 nanoparticles, and preparing the ceramic coating through the sol-gel process further enhances the mechanical properties of the material.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A steel plate for automobile chassis parts, characterized in that: The steel plate comprises: 0.03-0.05wt% C, 0.01-0.025wt% Si, 0.2-0.45wt% Mn, 0.02-0.1wt% V, 0.01-0.05wt% Nb, 0.01-0.025wt% P, 0.005-0.015wt% S, and the remainder is Fe and inevitable impurity elements; the steel plate is coated by austenitizing, martensite generation multi-stage heat treatment and sol-gel process.
2. A process for preparing a steel plate for automobile chassis parts according to claim 1, characterized in that: The process includes: Smelting, continuous casting, hot rolling, pickling and cold rolling, cleaning, heat treatment and coating.
3. The process for preparing a steel plate for automobile chassis parts according to claim 2, characterized in that: The hot rolling is to heat the ingot to 1100-1300°C and maintain it for 40-60 minutes; the pickling cold rolling is to pass the hot rolled steel plate through a pickling line, pickle it with a 1-5wt% hydrochloric acid solution for 1-5 minutes to remove the oxide scale and impurities on the surface, and then wash it with water to remove the residual acid solution. The pickled steel plate is rolled through a cold rolling mill at room temperature and then annealed at 600-700°C.
4. The process for preparing a steel plate for automobile chassis parts according to claim 2, characterized in that: The heat treatment comprises: heating the steel plate at 850-950°C to transform the structure of the steel into austenite; rapidly cooling the steel plate to 200-250°C slightly lower than the martensite starting temperature, maintaining the temperature for 30-60 minutes, and then heating the steel plate to a moderate partitioning temperature of 250-450°C to diffuse the carbon in the martensite into the austenite, further stabilizing the untransformed austenite, and cooling the steel plate to room temperature to form high-strength tempered martensite and stable residual austenite.
5. The process for preparing a steel plate for automobile chassis parts according to claim 2, characterized in that: The coating is prepared by a composite sol-gel process combined with different nanoparticles, and the preparation steps are: (1) Dissolve the precursor material in anhydrous ethanol, mix well, stir at 20-40° C., adjust the pH to 2-4 with 1 M dilute hydrochloric acid, and let stand for 20-60 hours to obtain a sol; (2) adding nanoparticles and a dispersant to the sol, stirring and ultrasonicating for 30-60 minutes to prepare a nanosol; (3) using dip coating, spray coating or spin coating to evenly cover the surface of the steel plate with the nanosol, and drying it at 20-80° C. to convert the nanosol into a gel to initially form a coating; (4) The coated steel plate is heated and sintered to convert the gel into a dense ceramic coating.
6. The process for preparing a steel plate for automobile chassis parts according to claim 5, characterized in that: The precursor materials in step (1) are tetraisopropyl titanate and ethyl silicate, and the mass ratio of tetraisopropyl titanate, ethyl silicate and anhydrous ethanol is 1:1:5-10.
7. The process for preparing a steel plate for automobile chassis parts according to claim 1, characterized in that: In step (2), the dispersant is at least one of polyvinyl alcohol, polyacrylic acid and polyethylene glycol; the nanoparticles are ZrO2 and Al2O3; and the mass ratio of the nanoparticles, the dispersant and the sol is 5-20:1-10:70-94.
8. The process for preparing a steel plate for automobile chassis parts according to claim 1, characterized in that: The heating and sintering temperature in step (2) is 200-500°C.
Citation Information
Patent Citations
Nanoparticle sol-gel composite hybride transparent coating materials
CN102015934A
Plated steel plate
CN107532266A
High-temperature corrosion-resistant coating and preparation method thereof, and high-temperature corrosion-resistant material
CN107903071A
Preparation method of composite anticorrosive coating for inner wall of garbage incinerator
CN110616420A
High-strength steel sheet and method for producing same
CN118804993A
Cited By
Preparation process of wear-resistant steel plate
CN121538391A